The first 30 years of the story of the Journal of Human Systems. Issue 1 (1st February 2021) - Stratton, Peter; Hanks, Helga
We are writing this story of Human Systems with excitement and an eye to the future. Rudi Dallas and Becky Stancer took on the editing of the Journal but also joined with Peter Stratton and Helga Hanks in looking for a new base for the Journal. They succeeded in having Sage Publications include the Journal in their publications in internet form with Rudi Dallas and Becky Stancer as editors. This is a fantastic new beginning, in a contemporary format and with a new orientation of Therapy, Culture and Attachment . Peter Stratton and Helga Hanks have undertaken to give context to this new beginning by writing about the previous thirty-year history of Human Systems.